Study of Zγ events and limits on anomalous ZZγ and Zγγ couplings in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2005)
We present a measurement of the Zγ production cross section and limits on anomalous ZZγ and Zγγ couplings for form-factor scales of Λ=750 and 1000 GeV. The measurement is based on 138 (152) candidates in the eeγ (μμγ) final state using 320(290)pb-1 of pp̄ collisions at s=1.96TeV. The 95% C.L. limits on real and imaginary parts of individual anomalous couplings are |h10,30Z|<0.23, |h20,40Z|<0.020, |h10,30γ|<0.23, and |h20,40γ|<0.019 for Λ=1000GeV. © 2005 The American Physical Society.